Encyclopedia of the Palestinians - Mattar, Philip, 1944- (Facts on File library of world history.)
"The scholarship and the balanced nature of a controversial, highly partisan issue are what make this volume important and useful to students of current events. The articles are clear and accessible, and discuss the political movements, arts, customs, and individuals that have made an impact on the Palestinian world."--"Outstanding Reference Sources," American Libraries, May 2001.